Analisis Kesulitan Mahasiswa Dalam Mengerjakan Soal Ujian Semester Akuntansi Perpajakan Ditinjau Dari Aspek Kognitif Dan Media Pembelajaran Pada Mahasiswa Program Studi Pendidikan Akuntansi Angkatan 2014 Universitas Muhammadiyah Surakarta - Bilitania, Tiara; , Dr. Wafrotur Rohmah (2016)
The purpose of this research are: 1) To determine the effect of cognitive abilities possessed ability students in doing the semester exam subjects Tax Accounting. 2) To determine the effect of instructional media students in doing the semester exam subjects Tax Accounting. 3) To determine the effect of cognitive abilities and learning media are owned by students in doing the semester exam subjects Tax Accounting. This type of research is associative research with quantitative approach to drawing conclusions through statistical methods. This study uses quantitative methods associative. The population in this study were students of Accounting Education who took a course in Tax Accounting class of 2014 is 217 students. The sampling technique using Random Sampling Proportional as many as 135 respondents. The necessary data and documentation obtained through a questionnaire that has previously been tested by validity and reliability testing. Data analysis technique used is multiple linear regression, F test, t-test, R2, and the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 9.987 0,331X1+0,352X2. The conclusion that can be drawn from this equation are: 1) "There is an effect of cognitive ability to the difficulties students in doing the exam half Tax Accounting" is acceptable. This is evident through hypothesis test (t test), which showed that the value t count > t table is 5,184> 1,978 with significance probability value <0.05, namely 0.000 and effective contribution (SE) of 19.4%. 2) "There is a Media Influence Learning Difficulties students to work on the problems semester exams Tax Accounting" can be accepted based on the hypothesis test (t test), which is known that t count > t table namely 5.411> 1.978 with significance probability value <0.05, is 0.000 and effective contribution (SE) of 20.6%. 3) "There is an effect of cognitive abilities and learning media to the difficulties students in doing the exam half Tax Accounting" unacceptable demonstrated through F test, which indicates the value of F count > F table is 44.039> 3.065 and significant probability value of 0.05, the coefficient 0,000 determination (R2) by 40% while the remaining 60% is influenced by other variables outside the study.